2022
DOI: 10.1101/2022.05.26.493528
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantifying portable genetic effects and improving cross-ancestry genetic prediction with GWAS summary statistics

Abstract: Polygenic risk scores (PRS) calculated from genome-wide association studies (GWAS) of Europeans are known to have substantially reduced predictive accuracy in non-European populations, limiting its clinical utility and raising concerns about health disparities across ancestral populations. Here, we introduce a novel statistical framework named X-Wing to improve predictive performance in ancestrally diverse populations. X-Wing quantifies local genetic correlations for complex traits between populations, employs… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 86 publications
1
7
0
Order By: Relevance
“…First, we allow our method to incorporate LD information. We note that this extension is similar to some recent work built on our initial PUMAS paper 37,39 . Second, we allow the method to partition full GWAS summary statistics into more than two datasets for various analytical purposes.…”
Section: Methodssupporting
confidence: 74%
See 2 more Smart Citations
“…First, we allow our method to incorporate LD information. We note that this extension is similar to some recent work built on our initial PUMAS paper 37,39 . Second, we allow the method to partition full GWAS summary statistics into more than two datasets for various analytical purposes.…”
Section: Methodssupporting
confidence: 74%
“…It is an important future direction to systematically optimize and benchmark PRS for diverse ancestral populations which would require incorporation of multiple sets of ancestry-specific GWAS and LD references. Although we did not explore this topic in this paper, our recent work introduced parallel ideas to tackle the challenges in multi-ancestry genetic risk prediction 39 . Second, analyses in this study were limited to GWAS summary statistics computed from independent samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that prediction performance can be improved when using ancestry-matched tuning cohorts for PRS construction to fine-tune hyper- parameters and avoid overfitting, such as P+T and the PRS-CS grid models explored in this study. While other studies have also explored options such as pseudo-validation when no additional tuning cohort is available 40,41…”
Section: Discussionmentioning
confidence: 99%
“…While other studies have also explored options such as pseudo-validation when no additional tuning cohort is available 40,41 Third, the practical considerations for target populations involved in PRS analyses are quite consistent between using homogenous GWAS and multi-ancestry GWAS. In this study, we used biobanks with various ancestry compositions and recruitment strategies as the target cohorts 19 .…”
Section: Discussionmentioning
confidence: 99%